Media Pembelajaran Berbasis IT - Syahputra, Randi; Prayoga, Tegar; Chandra, Zaki (Journal of Information Systems and Management (JISMA), 2024)
Instructional media is a tool that can assist the teaching and learning process, making the conveyed message clearer and ensuring that educational or instructional objectives are achieved effectively and efficiently. Learning outcomes are the results given to students as assessments after participating in the learning process by evaluating their knowledge, attitudes, and skills, leading to behavioral changes. Instructional media functions as one of the learning resources for students to receive the messages and information provided by the teacher, enhancing the learning materials and building knowledge for students. The benefits of instructional media are twofold. First, it provides guidance for teachers to achieve the learning objectives, enabling them to present the learning materials systematically and in an engaging manner, thus improving the quality of instruction. Second, it can boost students' motivation and interest in learning, allowing them to think critically and analyze the subject matter presented by the teacher in an enjoyable learning environment. Students can easily grasp the learning materials, resulting in improved learning outcomes. The use of instructional media can enhance students' learning outcomes in several ways: Simplifying the teaching and learning process, making it easy for students to comprehend and understand the lessons; Increasing the efficiency of student learning by aligning it with the learning objectives; Promoting student concentration in learning due to engaging and relevant instructional media; Elevating students' motivation to learn as their interest in the subject matter grows; Offering a comprehensive learning experience, enabling students to gain a practical understanding of the provided materials; and Involving students in the learning process, making them active participants, and providing opportunities for creativity and potential development.